Developmental study of small intestine in local chicken (pre hatch) (gulls gulls domesticate ) - Ban Hamza Abd; Fatimah Swadi Zghair; Maha Abdul-Hadi Abdul-Rida Al-Abdula (Diyala Journal for Veterinary Sciences, 2024)
Aims: The aim of this research was to found developed small intestine mucosa pre hatching and first two weeks of the life local domestic chicken, also the importance of carbohydrates in various chemical reactions, to study their distribution using special dyes, such as: combined AB-PAS (PH-2.5). Methods: The study is performed on 90 commercial of fertile eggs obtained from birds market, where it is place in a small incubator and incubated with (37.5ºC) and humidity (60%). Result: There is a strong correlation between the intestinal epithelium’s early development and the growth and feed efficiency of local chicken. This study’s goal was to record the morphological, histological, and histochemical evolution of the) duodenal, jejunum, and ileum ( mucosa in local chicken prehatch from days 15 to 21 of incubation. One hundred embryos or poults had their intestinal samples taken, and these were examined under both light and dissecting microscopy. The villus height increases significantly during which time, the junctional complex progressively tightens the epithelial cells’ apical end, and mature goblet cells become evident near the tip of the apical of the villi. The Villus height rises gradually till it reaches a plateau after 21 days. Before hatching, the shape of the villi gradually converts projections that resemble fingers to those that resemble leaves around 21 day. The significant morphological changes caused by consuming amniotic fluid before to hatch, as well as nutritional variables, in the local chicken gut epithelium.